2017
DOI: 10.1097/md.0000000000007962
|View full text |Cite
|
Sign up to set email alerts
|

Allergic shock caused by ingestion of cooked jellyfish

Abstract: Rationale:Although anaphylaxis caused by jellyfish stings is common in coastal areas, an allergic shock caused by cooked jellyfish ingestion has never been reported in China. In this paper, we report a case of allergic shock being caused by ingestion of cooked salt-preserved jellyfish shortly after being stung by a live jellyfish.Patient concerns:A 26-year-old Chinese man presented with dizziness, pruritus, dyspnea, hypotension, and tachycardia after eating cooked salted jellyfish. The patient had been stung t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The studies included in the final synthesis show that patients with allergies to crustaceans, cephalopods, mollusks, seafood and fish can consume jellyfish without increasing risk of an allergic reaction [17,19]. Three case reports of anaphylaxis have occurred after eating raw jellyfish [33][34][35], while one article written by Li et al [18] describes an episode of anaphylaxis after eating jellyfish that were not only salt-preserved but also cooked. Moreover, it would be appropriate to know if, in the presented case report, the jellyfish have been prepared correctly, eliminating all the non-edible parts like the stinging tentacles and the reproductive and digestive tracts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies included in the final synthesis show that patients with allergies to crustaceans, cephalopods, mollusks, seafood and fish can consume jellyfish without increasing risk of an allergic reaction [17,19]. Three case reports of anaphylaxis have occurred after eating raw jellyfish [33][34][35], while one article written by Li et al [18] describes an episode of anaphylaxis after eating jellyfish that were not only salt-preserved but also cooked. Moreover, it would be appropriate to know if, in the presented case report, the jellyfish have been prepared correctly, eliminating all the non-edible parts like the stinging tentacles and the reproductive and digestive tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies have been included in the final synthesis that refer to this risk. A case report by Li et al [18] showed a 26-year-old Chinese male that developed symptoms of erythema, pruritus, and palpitation half an hour after eating cooked salt-preserved jellyfish. He exhibited dizziness, dyspnea, and tachycardia.…”
Section: Allergenic Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [ 84 ] report a case study about a Chinese man (26 years old) who consumed cooked salt-preserved jellyfish and had erythema, pruritus and tachycardia, dizziness and dyspnea. This man was healthy without a medical history of any allergies to drugs and/or other substances, but was violently stung by jellyfish some 6 months before.…”
Section: Potential Risks Related To Eating Jellyfishmentioning
confidence: 99%